Inflammatory parameters mediates the relationship between dietary index for gut microbiota and frailty in middle-aged and older adults in the United States: findings from a large-scale population-based study - Yang, Qijiang; Wu, Xiaoyun; Duan, Jinlan; Chen, Yiyin; Yang, Tianrui (Frontiers in Nutrition, 2025)
BackgroundFrailty is a prevalent geriatric syndrome marked by diminished physiological reserves and heightened vulnerability to stressors, leading to adverse health outcomes and imposing significant economic burdens on healthcare systems.MethodsThis study investigates the relationship between the Dietary Index for Gut Microbiota (DI-GM) and the risk of frailty in middle-aged and older adults, using data from the National Health and Nutrition Examination Survey (NHANES) collected from 2007 to 2018. Weighted logistic regression, subgroup analysis, and restricted cubic splines (RCS) were performed to evaluate the relationship between DI-GM and frailty risk. Additionally, a mediation analysis was conducted to investigate the influence of relevant inflammatory parameters from complete blood count, including leukocyte count, neutrophil count, the neutrophil to lymphocyte ratio (NLR), and the systemic inflammatory response index (SIRI), to elucidate how DI-GM may influence the onset and progression of frailty.ResultsIn this cross-sectional analysis of 8,695 participants with a mean age of 65.56 years, 3,173 individuals were classified as frail. After adjusting for all covariates, a significant inverse relationship was observed between DI-GM and the risk of frailty. Quartile analysis revealed that participants in the highest quartile of DI-GM had significantly lower odds of frailty compared to those in the lowest quartile (OR: 0.80, 95% CI: 0.65–0.99, p = 0.04). Trend analyses across all models demonstrated a consistent inverse relationship between higher DI-GM quartiles and frailty odds (p < 0.0001 for the crude model; p = 0.001 for Model 1; p = 0.04 for Model 2). Subgroup analyses confirmed the stability of the impact of DI-GM on frailty risk across various subgroups. RCS showed that the risk of frailty decreased linearly with increasing DI-GM levels. Mediation analysis indicated significant effects for leukocyte count, neutrophil count, NLR, and SIRI, with mediation proportions of 5.7, 7.9, 4.4, and 5.5%, respectively (all p < 0.001).ConclusionThe levels of DI-GM are inversely associated with the risk of frailty, with part of this association mediated by inflammatory parameters.